A Novel Approach for the Genetic Analysis of Biliary Tract Cancer Specimens Obtained Through Endoscopic Ultrasound-Guided Fine Needle Aspiration Using Targeted Amplicon Sequencing. Issue 3 (March 2019) - Hirata, Koji; Kuwatani, Masaki; Suda, Goki; Ishikawa, Marin; Sugiura, Ryo; Kato, Shin; Kawakubo, Kazumichi; Sakamoto, Naoya
Abstract : OBJECTIVES: Biliary tract cancer (BTC) is an aggressive malignant tumor, and biomarker-based clinical trials for this cancer are currently ongoing. Endoscopic ultrasound–guided fine needle aspiration (EUS-FNA) is a safe procedure and enables pathological diagnoses; however, it is uncertain whether a tiny tumor sample of BTC obtained through EUS-FNA can be analyzed for diverse genetic alterations in the development and tolerance of BTC. Thus, we aimed to verify the feasibility of genetic analyses with EUS-FNA samples of BTC. METHODS: Targeted amplicon sequencing using a cancer gene panel with 50 genes was performed with tissue samples of 21 BTC patients obtained through EUS-FNA with a novel rapid on-site process compared with paired peripheral blood samples. RESULTS: Pathogenic gene alterations were successfully identified in 20 out of 21 patients (95.2%) with EUS-FNA specimens of BTC, which included 19 adenocarcinomas and 2 adenosquamous carcinomas. Eighty single nucleotide variants and 8 indels in 39 genes were identified in total, and 28 pathogenic alterations in 14 genes were identified (average, 1.4 alterations per patient). The most common alterations were TP53, KRAS, and CDKN2A in gallbladder carcinoma; TP53, KRAS, PIK3CA, and BRAF in intrahepatic cholangiocarcinoma; and TP53 and SMAD4 in extrahepatic cholangiocarcinoma. Actionable gene alterations (BRAF, NRAS, PIK3CA, and IDH1) were identified in 7 out of 21 patients. CONCLUSIONS: A novel approach in genetic analysis using targeted amplicon sequencing with BTC specimens obtained through EUS-FNA was feasible and enabled us to identify genomic alterations.